Le théâtre de Césaire, écritures-réécritures, un travail de Sisyphe - Daniel Delas (Continents manuscrits)
Daniel Delas comes back to the profuse theatrical re-writings by Césaire and investigates the following hypothesis : it is finally the questionning about the black leader of Afro-Caribbean independencies and, more widely, about the human being emancipation that haunts Césaire during more than thirty years and remains the core of all his writings, non only theatrical ones, nut also poetic and argumentative. Thereby, Césaire tries to create "a theater acting philosophically at all levels of whole human being."